UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN PISANG AMBON (Musa paradisiaca L.) TERHADAP TIKUS PUTIH (Rattus norvegicus L.) YANG DIINDUKSI KARAGENAN - Sukmawati Sukmawati; Yuliet Yuliet; Ririen Hardani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Anti-inflammatory activity test of ethanolic extract of banana leaf (Musa Paradisiaca L.) on carrageenan-induced paw edema in white male rats (Rattus novergicus L.) has been conducted. It was aimed to investigate and to determine the anti-inflammatory activity and its effective dose. The extract was prepared by maceration method using ethanol 96%. Anti-inflammatory activity test was performed in five different groups. Each group consisted of 5 rats. The 1st group (negative control) was given 0.5% CMC-Na suspension; the 2nd group (positive control) was given diclofenac sodium 9 mg/KgBW; the 3rd, 4th, and 5th groups were successively given the banana leaf extract as much as 500, 750 and 1000 mg/KgBW. Each rat was then induced by 1% carrageenan and tested using subplantar method.  The inflamed paw diameter was measured using a calliper while the inflamed paw volume using pletysmometer. The measurements were done for 6 hours long with intervals of 60 minutes. The data was statistically analyzed using ANOVA (analysis of variance). The results showed that the negative control had a significant difference with the other treatment groups which did not show any anti-inflammatory effect. In conclusion, ethanolic extract of banana leaf has effective anti-inflammatory activity at a dose of 750 mg/KgBW